Trauma Ginjal pada Kecelakaan dengan Kecepatan Tinggi - Annisa Humaira; Fadhli Hasan (Lembaga Pengembangan Kinerja Dosen, 2025)
Kidney trauma is a relatively common urological injury, often resulting from high-speed motor vehicle accidents, falls, or violent incidents. The kidneys are vulnerable to both blunt and penetrating trauma, with blunt mechanisms accounting for approximately 90% of all renal injuries. This paper reviews the anatomy of the kidney, mechanisms of injury, classification according to the American Association for the Surgery of Trauma (AAST), diagnostic evaluation, imaging modalities, and current management strategies. Most renal traumas are managed conservatively based on hemodynamic stability, while surgical exploration is indicated in severe or vascular injuries. Understanding the mechanism of injury and applying appropriate diagnostic evaluations are essential to determine the correct management approach and improve patient outcomes. Moreover, advancements in imaging techniques, such as CT scans, have significantly improved the accuracy of diagnosing renal injuries. Early intervention and appropriate monitoring are crucial in preventing complications such as hemorrhage or renal failure. This review aims to provide a comprehensive overview of renal trauma management to aid clinicians in improving patient care and optimizing recovery.